Ziemia obiecana - Wajda, Andrzej, 1926-; Olbrychski, Daniel; Seweryn, Andrzej; Pszoniak, Wojciech, 1942-; Reymont, Wladyslaw Stanislaw, 1867-1925.; Przedsiebiorstwo Realizacji Filmow "Zespoly Filmowe."; Zespol Filmowy "X."; Film Polski; Polart (Firm) (Sarasota, FL : Polart, distribution USA, 1995)
Three industrialists representing different ethnic groups in Poland, build a textile factory in Lodz at the turn of the century, but encounter problems with overworked, underpaid workers.
In Polish with English subtitles.
Title on container: Land of promise.
Based on the novel: Ziemia obiecana = The Promised land / Wl.St. Reymont.
Originally produced as motion picture in 1975.
"V273"--Label.
Director, Andrzej Wajda ; music, Wojciech Kilar.
Keywords: Industrialists -- Poland -- Drama; Feature films. -- Poland; Foreign films